State and culture in sustainability transformations: structural power, democracy, and the promise of a Marcusian cultural politics of critical meaning-making - Marit Hammond (Sustainability: Science, Practice, & Policy)
The concept of sustainability transformation highlights the need not merely for new environmental policies but for transformational change of societal systems in response to the ecological crisis, including a profound shift in values, ideas, and cultural meanings. Yet, according to historical-institutionalist state theory, the imperatives of the liberal-capitalist democratic welfare state give rise to a “glass ceiling” of transformation that limits prospects for such systemic change beyond quality-of-life improvements that remain consistent with liberal capitalism. Exploring the potential of cultural meaning-making to break this glass ceiling, I draw on various strands of critical theory to identify the operation of ideological power at the level of both the state and the cultural realm as what creates the glass ceiling of transformation. This makes the cultural realm at once a possible emancipatory force and a site of domination of its own. I suggest that the critical thought of Herbert Marcuse offers an account of a critical-democratic culture that promises to arise precisely out of this ambiguity and that must be understood as a crucial foundation for sustainability transformation.